Assessment of the Induced Electric Fields in a Carbon-Fiber Electrical Vehicle Equipped with a Wireless Power Transfer System - Valerio De Santis (Energies, 2018)
In this study, the electric field induced inside two realistic anatomical models placed near or inside an electric vehicle made of carbon-fiber composite while charging its battery with a wireless power transfer (WPT) system has been investigated. The WPT source consists of two parallel inductive coils operating with a power output of 7.7 kW at two different frequencies of 85 and 150 kHz. Since a misalignment between the primary and the secondary coil creates higher induced fields, a misalignment of 20 cm is also considered as the worst-case exposure condition. The analysis of the obtained results shows that the International Commission on Non-Ionizing Radiation Protection (ICNIRP) basic restrictions are exceeded by 1.3 dB and 4.8 dB for the aligned and misaligned coil positions, respectively. This exceedance is however confined only in a small area of the driver’s foot.